agent‐based simulation of a release process for encapsulated flavour using the NetLogo platform - Zandi, M; Mohebbi, M (Flavour and fragrance journal, 2015)
In this study we developed an agent‐based model that simulates the release process of encapsulated flavour in different situations. Our model was built in the NetLogo platform, which is a multi‐agent programming language and modelling environment with a good documentation, user‐friendly environment and visualization abilities. The main aim of the work presented is to provide a model that will easily predict the release of encapsulated flavour. In this work we use the model developed to evaluate the flavour‐release properties (such as release time and rate) dependent upon input parameters. Release data of the encapsulated diacetyl (2,3‐butanedione) from alginate–whey‐protein concentrate microcapsules were then used for model validation. Results show that this model can simulate the release‐flavour process well, and there is a good correlation between experimental and model release data. Results also suggested that the flavour‐release process can easily be predicted using this agent‐based model.